Intracellular Vesicle Trafficking Genes, RabC-GTP, Are Highly Expressed Under Salinity and Rapid Dehydration but Down-Regulated by Drought in Leaves of Chickpea (Cicer arietinum L.) - Khassanova, Gulmira; Kurishbayev, Akhylbek; Jatayev, Satyvaldy; Zhubatkanov, Askar; Zhumalin, Aybek; Turbekova, Arysgul; Amantaev, Bekzak; Lopato, Sergiy; Schramm, Carly; Jenkins, Colin; Soole, Kathleen; Langridge, Peter; et al. (Frontiers in Genetics, 2019)
Intracellular vesicle trafficking genes, Rab, encoding small GTP binding proteins, have been well studied in medical research, but there is little information concerning these proteins in plants. Some sub-families of the Rab genes have not yet been characterised in plants, such as RabC - otherwise known as Rab18 in yeast and animals. Our study aimed to identify all CaRab gene sequences in chickpea (Cicer arietinum L.) using bioinformatics approaches, with a particular focus on the CaRabC gene sub-family since it featured in an SNP database. Five isoforms of the CaRabC gene were identified and studied: CaRabC-1a, -1b, -1c, -2a and -2a*. Six accessions of both Desi and Kabuli ecotypes, selected from field trials, were tested for tolerance to abiotic stresses, including salinity, drought and rapid dehydration and compared to plant growth under control conditions. Expression analysis of total and individual CaRabC isoforms in leaves of control plants revealed a very high level of expression, with the greatest contribution made by CaRabC-1c. Salinity stress (150 mM NaCl, 12 days in soil) caused a 2-3-fold increased expression of total CaRabC compared to controls, with the highest expression in isoforms CaRabC-1c, -2a* and -1a. Significantly decreased expression of all five isoforms of CaRabC was observed under drought (12 days withheld water) compared to controls. In contrast, both total CaRabC and the CaRabC-1a isoform showed very high expression (up-to eight-fold) in detached leaves over six hours of dehydration. The results suggest that the CaRabC gene is involved in plant growth and response to abiotic stresses. It was highly expressed in leaves of non-stressed plants and was down-regulated after drought, but salinity and rapid dehydration caused up-regulation to high and very high levels, respectively. The isoforms of CaRabC were differentially expressed, with the highest levels recorded for CaRabC-1c in controls and under salinity stress, and for CaRabC-1a – in rapidly dehydrated leaves. Genotypic variation in CaRabC-1a, comprising eleven SNPs, was found through sequencing of the local chickpea cultivar Yubileiniy and germplasm ICC7255. Amplifluor-like markers based on one of the identified SNPs in CaRabC-1a were designed and successfully used for genotyping chickpea germplasm.